2002
DOI: 10.1074/jbc.m205104200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Charge Properties of Bacterial Envelope in Bactericidal Action of Human Group IIA Phospholipase A2against Staphylococcus aureus

Abstract: S. aureus, we examined the effects of mutations that prevent specific modifications of cell wall (dltA) and cell membrane (mprF) polyanions. In comparison to the parent strain, isogenic dltA ؊ bacteria are ϳ30 -100؋ more sensitive to PLA 2 , whereas mprF ؊ bacteria are <3-fold more sensitive. Differences in PLA 2 sensitivity of intact bacteria reflect differences in cell wall, not cell membrane, properties since protoplasts from all three strains are equally sensitive to PLA 2 . A diminished positive charge in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
145
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(157 citation statements)
references
References 50 publications
7
145
0
3
Order By: Relevance
“…In marked contrast, human group IIA sPLA 2 shows a dramatic dependence on the presence of Ͼ10 -20% anionic phosphatidylserine for binding to vesicles (10,20,21), which is consistent with its well established function as a Gram-positive bactericidal agent (22)(23)(24). Gram-positive membranes are highly rich in acidic phospholipids, especially phosphatidylglycerol, and the high density of basic residues (lysines and arginines) on the surface of the group IIA enzyme is important for allowing this enzyme to penetrate the highly anionic cell wall of Gram-positive bacteria (25,26).…”
Section: Discussionmentioning
confidence: 76%
“…In marked contrast, human group IIA sPLA 2 shows a dramatic dependence on the presence of Ͼ10 -20% anionic phosphatidylserine for binding to vesicles (10,20,21), which is consistent with its well established function as a Gram-positive bactericidal agent (22)(23)(24). Gram-positive membranes are highly rich in acidic phospholipids, especially phosphatidylglycerol, and the high density of basic residues (lysines and arginines) on the surface of the group IIA enzyme is important for allowing this enzyme to penetrate the highly anionic cell wall of Gram-positive bacteria (25,26).…”
Section: Discussionmentioning
confidence: 76%
“…The absence of dlt in S. aureus results in a high susceptibility to being killed by neutrophils and also reduces the ability to colonize plastic or glass surfaces, a factor in catheterassociated infection (Collins et al, 2002;Gross et al, 2001). In addition, it has been found that a dlt mutant is highly susceptible to human phospholipase A 2 , a cationic protein that exhibits antibacterial activity against S. aureus, owing to a strong surface negative charge (Koprivnjak et al, 2002). Furthermore, dlt in group A streptococci has been found to promote survival in neutrophils and invasion of epithelial cells (Kristian et al, 2005), and dlt in Streptococcus agalactiae and Listeria monocytogenes is associated with susceptibility to phagocytic cells (Abachin et al, 2002;Poyart et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously clarified that lysozyme, sPLA2, -defensin1 and β-defensin2 are secreted mainly from exocrine glands associated with the upper alimentary tract, but only lysozyme and sPLA2 are also secreted from the Paneth cells in the small intestine [29]. Lysozyme mainly acts against Gram-positive bacteria, and several Gram-negative bacteria [1,12], as well as sPLA2 [13,16]. α-defensins and β-defensins act for both Gram-positive and Gram-negative bacteria [4,6,15].…”
Section: Discussionmentioning
confidence: 99%